Climate policy as expectation management? - Daiju Narita (Kiel Institute for the World Economy (IfW), 2010)
It is believed that the primary economic solution to climate change is an introduction of a carbon pricing system anchored to the social cost of carbon, either as a form of tax or tradable permits. Potentially significant externalities accompanying the introduction of emission-reducing technologies, however, imply that the standard argument does not capture some important aspects for the designing of climate policy such as expectation-driven technology adoption. By using a simple model, we show some possible cases where carbon emission reduction progresses in a self-fulfilling prophecy by firms expecting others' future actions. In such circumstances, the carbon pricing system does not have much influence on determining the final outcome of economy-wide emission reduction. This highlights the danger of overemphasis on finding the 'right' carbon price in policy making and the role of climate policy as expectation management.
Keywords: Q54; O33; 330; Climate policy; technology choice; expectations; multiple equilibria; Klimaschutz; Ökosteuer; Emissionsrechte; Erwartungstheorie; Umwelttechnik; Technologiewahl; Gleichgewicht; Theorie